2022
DOI: 10.1371/journal.pgph.0000206
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for third-generation cephalosporin-resistant and extended-spectrum β-lactamase-producing Escherichia coli carriage in domestic animals of semirural parishes east of Quito, Ecuador

Abstract: Extended-spectrum β-lactamase (ESBL)-producing and other antimicrobial resistant (AR) Escherichia coli threaten human and animal health worldwide. This study examined risk factors for domestic animal colonization with ceftriaxone-resistant (CR) and ESBL-producing E. coli in semirural parishes east of Quito, Ecuador, where small-scale food animal production is common. Survey data regarding household characteristics, animal care, and antimicrobial use were collected from 304 households over three sampling cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 97 publications
(192 reference statements)
1
3
0
Order By: Relevance
“…Our results are consistent with the increase in ESBL-producing E. coli reported in dogs worldwide, mainly related to the high use of β-lactams in clinical practice in veterinary medicine [34,35]. The percentage of samples possessing ESBL-producing E. coli was 13.3%, similar to other countries in the region, such as Ecuador [36]. In the comparison among isolates, we found 34.3% of ESBL producers, which is a lower percentage than that reported in Thailand [10].…”
Section: Antibiotic Patternsupporting
confidence: 89%
“…Our results are consistent with the increase in ESBL-producing E. coli reported in dogs worldwide, mainly related to the high use of β-lactams in clinical practice in veterinary medicine [34,35]. The percentage of samples possessing ESBL-producing E. coli was 13.3%, similar to other countries in the region, such as Ecuador [36]. In the comparison among isolates, we found 34.3% of ESBL producers, which is a lower percentage than that reported in Thailand [10].…”
Section: Antibiotic Patternsupporting
confidence: 89%
“…ESBL-producing E. coli are a major cause of antimicrobial-resistant infections and pose a major threat worldwide as they can cause infections that are difficult to treat in animals and humans [38]. The overall percentage of ESBL-producing E. coli strains in this study was 8.5%.…”
Section: Mdr and Esbl-producing E Coli Among Studied Isolatesmentioning
confidence: 69%
“…In contrast to our results, Fanta et al reported 73% E. coli isolates were ceftriaxone-resistant [ 11 ]. This may be due to the irrational use of third-generation cephalosporins [ 12 ]. However, a significant degree of susceptibility was found to nitrofurantoin followed by amikacin and gentamicin.…”
Section: Discussionmentioning
confidence: 99%